1994
DOI: 10.1515/cclm.1994.32.9.669
|View full text |Cite
|
Sign up to set email alerts
|

Lysosomes and Human Liver Disease: A Biochemical and Immunohistochemical Study of -Hexosaminidase

Abstract: Summary:Liver biopsies from 88 patients with different liver diseases were studied for ß-hexosaminidase activity. Liver specimens with normal light microscopical morphology showed no immunohistochemical reactivity for ß-hexosaminidase. Increased reactions were noted, mainly in hepatocytes, in biopsies from the patients with different liver diseases. A very large interindividual Variation of biochemical liver ß-hexosamindase activity occurred even within the same diagnostic group, and no group of patients showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Neopterin appears to be produced specifically by human activated monocytes/macrophages in response to interferon-γ produced by activated T lymphocytes (14,15). It has also been suggested that β-hexosaminidase (Hex) may also appear in some cases due to macrophage activation (16,17). An increase in its serum/plasma activity in patients with Gaucher's disease has been previously described (18)(19)(20), and may offer a useful approach to its diagnosis and screening (18).…”
Section: Introductionmentioning
confidence: 99%
“…Neopterin appears to be produced specifically by human activated monocytes/macrophages in response to interferon-γ produced by activated T lymphocytes (14,15). It has also been suggested that β-hexosaminidase (Hex) may also appear in some cases due to macrophage activation (16,17). An increase in its serum/plasma activity in patients with Gaucher's disease has been previously described (18)(19)(20), and may offer a useful approach to its diagnosis and screening (18).…”
Section: Introductionmentioning
confidence: 99%
“…The activity of the lysosomal enzymes is increased in liver disease (8,11,12). The reason for this is not known.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that serum lysosomal enzymes do not reflect the same liver cell function as the other parameters. The reason for the increased serum lysosomal enzyme activity in liver disease is not known, but several possible explanations have been discussed (8,11,12). We have previously speculated that since the degenerative process in the hepatocytes by itself leads to increased lysoso-ma1 enzyme activity in the hepatocytes, it might 10 explain increased serum lysosomal enzyme activity (8).…”
Section: Lysosomal Enzymesmentioning
confidence: 99%
“…Both isoenzymes recognize terminal N-acetylglucosamine and Nacetylgalactosamine, but only isoenzyme A recognizes 6-sulfated residues of these sugars (Winchester, 1996). HEX is active in most tissues and organs such as kidney (Skalova, 2005), spleen (Emiliani et al, 1999), liver (Elsafi et al, 1994), mucous membrane of stomach and intestine (Gil-Martin et al, 1999;Michaels & Hellequist, 2001), cortex (Hammarsund et al, 2004), lung (Baritussio et al, 2001;Minami et al, 1985), epidermal fibroblasts (Ichisaka et al, 1998), placenta (Arciuch et al, 1999) and neoplastic tissues (Bhuvarahamurthy & Govindsamy, 1996;Lerner, 1996;Matsuura et al, 2004). HEX is used as a marker for monitoring the course of sereval diseases like chronic glomerulonephritis (Bazzi et al, 2002), urinaemia (Linko-Lopponen, 1986;Stabellini et al, 2005), arterial hypertension (Perez-Blanco, 1996), Sjogren's syndrom (Sohar et al, 2005), advanced stadium of diabetes (Nakazawa & Tamai, 1991), rheumatoid arthritis (Popko et al, 2005), idiopathic juvenile arthritis (Popko et al, 2003), osteoarthritis (Liu et al, 2004) and for evaluation of kindney function after transplantation (Kotanko et al, 1996).…”
Section: E Olszewska and Othersmentioning
confidence: 99%